Strategizing Marketing Mix for Business Sustainability of Ethiopian MSEs - Meher, Kishor Chandra; Hamato, Gemechu Geda (Indian Journal of Marketing, 2022)
The medium and small-scale enterprises contribute immensely to the economic growth of Ethiopia. Hence, the long-term sustainability of this sector is vital for the economy. The captioned research aimed to assess the marketing mix strategies and their effect on the short and long-term sustainable advantage of MSEs. The research applied structural equation modeling with pre-run confirmatory factor analysis to investigate the causal analysis among the study’s variables. The study applied cluster sampling by taking the largest state Oromia and simple random sampling to obtain the responses through a Likert scaled questionnaire. The criterion variables are marketing performance and business sustainability, while marketing mix strategies are predictor variables. The CFA results revealed that the people and place variables were not eligible for applying SEM. The SEM results exhibited the hypothesized model as a perfect fit. Product strategy influenced the marketing performance, whereas there was a significant effect of product, process, and pricing strategies on the sustainability of MSEs’ businesses. The results hinted to the owners of MSEs to strengthen the strategic resources and apply the right tools by innovating differentiation of products to sustain value for the business.